Kodifikasi Hadis Imam Bukhari: Pendekatan Historis terhadap Metode Penyusunan dan Kontribusi dalam Ulumul Hadis: Penelitian - Fatma Amelia; M. Ulul Azmi; Arju Mushaffa; Muhammad Thoriqul Islam; Amit Dana Ikmah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to trace the historical process of hadith codification carried out by Imam al-Bukhari, particularly in the compilation of the book Shahih al-Bukhari, and to examine his contribution to the development of hadith science (ulumul hadith). Using a qualitative approach based on literature review, this study examines primary and secondary sources to understand the historical background, hadith selection strategies, and their impact on Islamic scholarly tradition. The findings reveal that Imam al-Bukhari applied a highly rigorous selection method, such as ensuring the continuity of the chain of transmission (sanad), the integrity of the narrators, and the consistency of the text (matan) with the fundamental principles of Islamic teachings. His work not only established scientific standards in hadith writing but also promoted the development of branches of knowledge such as musthalah al-hadith and jarh wa ta’dil. The book Shahih al-Bukhari remains the primary reference for evaluating authentic hadith and remains relevant in Islamic studies to this day.